(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the research of Devin Deweese, an orientalist and professor at Indiana University in the United States who has studied Muslim Oriental literature in all its aspects.The article reveals the professor Devin Deweese’s analysis of the period in which “Funun al-balaghah” was written, its language, the history of manuscript, his attempt to determine the significance of the manuscript in the literary process of that time and today. To substantiate his views, he has translated some parts of the manuscript into English and quoted it.